In silico identification of MicroRNAs targeting the key nucleator of stress granules, G3BP: Promising therapeutics for SARS-CoV-2 infection - Bjad K. Almutairy (Elsevier, 2021)
Stress granules (SGs) are non-membrane ribonucleoprotein condensates formed in response to environmental stress conditions via liquid–liquid phase separation (LLPS). SGs are involved in the pathogenesis of aging and aging-associated diseases, cancers, viral infection, and several other diseases. GTPase-activating protein (SH3 domain)-binding protein 1 and 2 (G3BP1/2) is a key component and commonly used marker of SGs. Recent studies have shown that SARS-CoV-2 nucleocapsid protein via sequestration of G3BPs inhibits SGs formation in the host cells. In this study, we have identified putative miRNAs targeting G3BP in search of modulators of the G3BP expression. These miRNAs could be considered as new therapeutic targets against COVID-19 infection via the regulation of SG assembly and dynamics.